Investigation of the Ιmpact of HVOF Spraying Parameters on the Abrasion Resistance of Tungsten Carbide Coatings - Nguyen, Hong Tien; Nguyen, Tuan Linh; Nguyen, Van Thien; Hoang, Long (Engineering, Technology & Applied Science Research, 2024)
For components operating under high pressure and high values of friction conditions, rapid wear is a common issue. Surface treatment measures are often employed to enhance the working lifespan of such components by improving their resistance to abrasion. This paper utilizes the Taguchi experimental design method in conjunction with Analysis of Variance (ANOVA) to assess the impact of spraying parameters on the abrasion resistance of the coating when applying the HVOF method. The sprayed material is WC HMSP1060-00+60% 4070, primarily consisting of Nickel and Tungsten Carbide, whereas the material for manufacturing the pressing screws is 1045 steel. The investigated spraying parameters include the spray Flow Rate (F), Spray Distance (D), and Oxygen/Propane Ratio (R). The experimental results are analyzed to determine the most suitable spraying parameters to achieve the highest abrasion resistance, and thereby improve the working lifespan of the components.